2021
DOI: 10.22541/au.162428051.17893357/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nitrite as a causal factor for nitrate-dependent anaerobic corrosion of metallic iron induced by Prolixibacter strains

Abstract: Microbially influenced corrosion (MIC) may contribute significantly to overall corrosion risks, especially in the gas and petroleum industries. In this study, we isolated four Prolixibacter strains, which belong to the phylum Bacteroidetes, and examined their nitrate-respiration- and Fe0-corroding activities, together with two previously isolated Prolixibacter strains. Four of the six Prolixibacter strains reduced nitrate under anaerobic conditions, while the other two strains did not. The anaerobic growth of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, in the presence of Fe 0 , nitrite increased until day 4, and decreased from day 7; ammonium increased more than in the absence of Fe 0 . This was demonstrated by nitrite-induced chemical corrosion of Fe 0 because nitrite oxidizes Fe 0 in a concentration-dependent manner, as previously shown (Iino et al, 2021b). Evidence that nitrite produced by biological nitrate reduction was the primary causal agent of Fe 0 corrosion is shown in Figure 2, where nitrite reduction occurred in parallel with Fe 0 oxidation.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Interestingly, in the presence of Fe 0 , nitrite increased until day 4, and decreased from day 7; ammonium increased more than in the absence of Fe 0 . This was demonstrated by nitrite-induced chemical corrosion of Fe 0 because nitrite oxidizes Fe 0 in a concentration-dependent manner, as previously shown (Iino et al, 2021b). Evidence that nitrite produced by biological nitrate reduction was the primary causal agent of Fe 0 corrosion is shown in Figure 2, where nitrite reduction occurred in parallel with Fe 0 oxidation.…”
Section: Discussionsupporting
confidence: 69%
“…Previously, Prolixibacter denitrificans and Prolixibacter sp. strain SD074, isolated from an oil well and a crude oil storage tank, have shown to corrode Fe 0 with concomitant nitrate reduction under anaerobic conditions (Iino et al, 2015(Iino et al, , 2021b. Iron corrosion by the nitrate-reducing bacterium I. nitroreducens Q-1 T has shown that MIC occurs not only under anaerobic conditions but also under aerobic conditions in oil fields and iodine production facilities.…”
Section: Discussionmentioning
confidence: 99%
“…To lessen the risk of sulphate corrosion in the complex storage tank, the optimum ratio of inoculating NRB to nitrate, nitrite, and molybdate was identified over a range of conditions. By using this measure, we were able to prevent sulphate-related damage to the reservoir [11].…”
Section: Introductionmentioning
confidence: 99%